Report of the six-week vocational/job-oriented project - The University of the West Indies, St. Augustine. Extra-Mural Studies Unit (Extra-Mural Studies Unit, UWI, 1987)
This report gives an account of a vocational/job-oriented project, based on the model developed at the Sangre Grande Centre of the Extra Mural Studies Unit of The University of the West Indies (UWI), which was mounted during the 1987 summer vacation period . It was a six-week intensive training programme on marketable skills and self-employment of young persons (18-25 years). This age range was chosen, because, according to government statistics, approximately 80,000 young persons in this age range were either unemployed or unemployable. The programme comprised 11 skill training projects--agriculture, applied arts, business studies, construction, crafts, decoration, electronics and electricity related, fashion and fabric, food preparation, mechanical and services, as well as personality and confidence development modules of self-awareness, drugs and unemployability, physical fitness and productivity, developing positive attitudes to work and study, and small business development. Part I of the report details the origin and characteristics of the programme, scheduling, methodology used, and provides recommendations on the actual construction and conduct of the training programme. Part II summarizes the actual operation of the programme and indicates that 98 percent of the participants succeeded in reaching the required standard. Part III comprises 13 appendices of material related to the course, including registration form, certificate of proficiency, and statistics on the number and work ages of unemployed persons seeking work
Keywords: Extra-Mural Studies Unit, UWI, St. Augustine